Harnessing the potential of N-heterocyclic carbenes for the rejuvenation of group-transfer polymerization of (meth)acrylics - Raynaud, Jean (2008)
(Chemical Equation Presented) Neutral but versatile: N-heterocyclic carbenes are very efficient catalysts for the group-transfer polymerization of acrylates and methacrylates in both polar and apolar media. These organocatalysts were also used to design all-(meth)acrylic di-and triblock copolymers.